Effect of Humic Acid on Spirulina plantisis Production and Analysis of Nutrient Contents - P.K. Dhanalakshmi, B. Anusha, P. Prakash*, (Recent Research in Science and Technology, 2011)
Spirulina is a microscopic blue-green alga in the shape of a spiral coil, used as a human dietary supplement, as well as a whole food, which was cultivated in different concentrations of humic acid such as 0.1%, to 0.7 %. The protein, chlorophyll, fatty acids levels measured at the end of the experiment in all concentrations. Among the concentration the maximum biomass was obtained from 0.2% of humic acid treated medium. The lower amount of biomass was obtained from above 0.5%.In this study, it was found that increased concentration of humic acid decreases the biomass of Spirulina plantensis. Thus it was concluded in this work, that lower concentration of humic acid increases the growth and nutrient contents of Spirulina plantensiss.